Absence of PARP‐1 affects Cxcl12 expression by increasing DNA demethylation - Tolić, Anja (J Cell Mol Med, 2019)
Poly [ADP‐ribose] polymerase 1 (PARP‐1) has an inhibitory effect on C‐X‐C motif chemokine 12 gene (Cxcl12) transcription. We examined whether PARP‐1 affects the epigenetic control of Cxcl12 expression by changing its DNA methylation pattern. We observed increased expression of Cxcl12 in PARP‐1 knock‐out mouse embryonic fibroblasts (PARP1−/−) in comparison to wild‐type mouse embryonic fibroblasts (NIH3T3). In the Cxcl12 gene, a CpG island is present in the promoter, the 5′ untranslated region (5′ UTR), the first exon and in the first intron. The methylation state of Cxcl12 in each cell line was investigated by methylation‐specific PCR (MSP) and high resolution melting analysis (HRM). Both methods revealed strong demethylation in PARP1−/− compared to NIH3T3 cells in all four DNA regions. Increased expression of the Ten‐eleven translocation (Tet) genes in PARP1−/− cells indicated that TETs could be important factors in Cxcl12 demethylation in the absence of PARP‐1, accounting for its increased expression. Our results showed that PARP‐1 was a potential upstream player in (de)methylation events that modulated Cxcl12 expression.